Synthesis and characterization of a new trans-2,2 '-azoquinoxaline bridged bisphthalocyanine - SALAN, ÜMİT (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
A new trans-2,2'-azoquinoxaline bridged bisphthalocyanine was synthesized from the corresponding quinoxaline-2(1 H)one oxime, which can be obtained by the reaction of s-trans-chloroethanedial with 2-(3,4-diaminophenoxy)-9,16,23-tri(hexylthio)phthalocyanine zinc(II). 2-(3,4-Diaminophenoxy)-9,16,23-tri(hexylthio)phthalocyanine zinc(II) was synthesized by reduction of 2-(4-amino-3-nitrophenoxy)-9,16,23-tri(hexylthio)phthalocyanine zinc(II). Novel compounds were characterized by elemental analysis, UV/vis, IR and H-1 NMR spectroscopy. The conductivity and the humidity sensing properties of spin coated films of these compounds were investigated by measuring the complex impedance spectra at different humidities. Films of the final product show Up to 10(3) orders of magnitude higher conductivity than the starting and intermediate compounds. The results indicate that the presence of water vapour always leads to a drop in the real and imaginary part of the complex impedance. At room temperature, the capacitance of the films exhibits reversible increase with relative humidity, which makes these films attractive for humidity sensing applications. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; azoquinoxaline; zinc complex; humidity sensing; impedance spectra; THIN-FILMS; HUMIDITY SENSORS; ELECTRODES; PORPHYRIN; REDUCTION; POLYMER